2020
DOI: 10.1111/plb.13189
|View full text |Cite
|
Sign up to set email alerts
|

Seed dormancy of Cardiospermum halicacabum (Sapindaceae) from three precipitation zones in Sri Lanka

Abstract: This study investigated seed germination of Cardiospermum halicacabum, a medicinally important invasive species. • We compared mass, moisture content (MC), dormancy and dormancy-breaking treatments and imbibition and germination of scarified and non-scarified seeds of C. halicacabum from a low-elevation dry zone (DZ), low-elevation wet zone (WZ1) and mid-elevation wet zone (WZ2) in Sri Lanka to test the hypothesis that the percentage of seeds with water-impermeable seed coats (physical dormancy, PY) decreases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…As an adaptive trait, deep seed dormancy appears to promote plant survival in high‐elevation habitats (Baskin & Baskin, 2014 ). Consistently, S. longifolia populations contain higher proportions of dormant seeds at high elevations (Cotado et al, 2020 ), Physalis species show an increase in dormant seeds with increasing elevation (Farooq et al, 2021 ), and C. halicacabum seeds show more complex seed dormancy at high elevations than at low elevations (Thusithana et al, 2021 ). These results suggest that natural selection pressure should favor plants that produce more dormant mature seeds at higher elevations.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…As an adaptive trait, deep seed dormancy appears to promote plant survival in high‐elevation habitats (Baskin & Baskin, 2014 ). Consistently, S. longifolia populations contain higher proportions of dormant seeds at high elevations (Cotado et al, 2020 ), Physalis species show an increase in dormant seeds with increasing elevation (Farooq et al, 2021 ), and C. halicacabum seeds show more complex seed dormancy at high elevations than at low elevations (Thusithana et al, 2021 ). These results suggest that natural selection pressure should favor plants that produce more dormant mature seeds at higher elevations.…”
Section: Discussionmentioning
confidence: 91%
“…Plants distributed over a wide range of elevations exhibit highly variable SDS due to different natural selection pressures (Allen & Meyer, 1998 ; Jurado & Flores, 2005 ; Veselá et al, 2020 ). For example, populations of Saxifraga longifolia (Saxifragaceae) from high elevations show the highest proportion of dormant seeds (Cotado et al, 2020 ), while Cardiospermum halicacabum (Sapindaceae) seeds collected from high‐elevation habitats show more complex SDS than seeds from low‐elevation habitats, requiring more periods of cold stratification to break dormancy (Orrù et al, 2012 ; Thusithana et al, 2021 ). Low‐elevation populations of wild grapevine ( Vitis vinifera subsp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to determining if a seed or other diaspore is water-permeable or impermeable, it is important to keep in mind that impermeability (i.e. PY) develops either during maturation drying on the mother plant or even during post-dispersal drying (Baskin and Baskin, 2014; Jaganathan, 2016, 2022; Thusithana et al, 2021). Seeds or fruits with PY become impermeable to water only when the moisture content (MC) of the diaspore falls below a species-specific MC threshold (see Table 6.2 in Baskin and Baskin, 2014); otherwise, the diaspore will remain water-permeable.…”
Section: Discussionmentioning
confidence: 99%
“…Gallará et al (2021) showed that the drupes of Lithraea molleoides (Anacardiaceae) needed post-dispersal drying for the induction of PY. However, in fact, the diaspore MC at which PY is induced also can vary even between populations of the same taxon growing under different environmental conditions (Thusithana et al, 2021). And furthermore, the development of PY does not occur at the same time for all seeds in the same days-after-pollination cohort and thus not at the same MC [see discussion in Qu et al (2010) and references cited therein].…”
Section: Discussionmentioning
confidence: 99%